Underlying relational dimensions of flow transitions along ring roads and their impacts on the typo-morphology of open spaces: two cases from Nordic countries. Issue 1 (1st January 2021) - Amr, Alia'a
ABSTRACT: This study explores the roles and functions of urban voids and their relationship with the built forms alongside ring roads. This investigation sheds light on the typo-morphology of open spaces in regard to the flow transitions (in substance, intensity, and/or direction) of ring roads, addressing several relational aspects between the built and non-built environments in two case studies: Greater Helsinki, Finland and Oslo, Norway. By using a descriptive mapping method, this study classifies open spaces and then qualitatively describes the levels and degrees of spatial and social interaction and exchange. In both case studies, new patterns of open spaces gradually evolved, in which their primary roles were not only to contain the physical exchange neutrally, but also to provide a symbolic spatial meaning and experience in accordance with the flow. This study describes six dimensions of flow transitions and their impacts on open spaces alongside ring roads and the levels of spatial and social interaction there. Finally, it calls for the adoption of new approaches to improve the existing networks of open spaces as binding elements alongside ring roads, where their emptiness and fragmentation could be used to overcome spatial inertia, discontinuity, and disintegration.